Study on patients with Clostridioides difficile infection during the COVID-19 pandemic in Bulgaria. Issue 1 (31st December 2023) - Velev, Valeri; Pavlova, Maria; Alexandrova, Ekaterina; Popov, Мetodi; Lutakov, Ivan; Tcherveniakova, Tatiana; Angelova, Andreana; Hristozova, Eli; Kalchev, Yordan; Ivanov, Ivan
Abstract: One of the most pressing public health problems is the misuse of antibiotics, especially in industrialized countries. In addition to antibiotic resistance, a disease associated with this abuse is Clostridioides difficile infection (CDI). It is also a serious problem in long-term hospital treatment, as it often causes intra-hospital infections. The coronavirus disease 2019 (COVID-19) pandemic has also led to widespread misuse of antibiotics and prolonged hospitalizations. The aim of our study was to compare two groups of patients who developed CDI before and during the COVID-19 pandemic, respectively. A total of 246 CDI patients with an average age of 58 years were studied for the period of March-August 2021, who also recovered from COVID-19. They were compared with another group of CDI patients who had become ill in the period before COVID-19. We found an increase in CDI patients for the period of the COVID-19 pandemic by 21.95%. Patients with CDI associated with COVID-19 were older, with higher rates of neurologic, tumor and cardiovascular disease, and with metabolic syndrome. In the group with COVID-19 CDI, there was higher use of proton pump inhibitors, use of antibiotics and significantly higher use of corticosteroids. All these factors lead to the conclusion that increased caution is needed in patients with COVID-19 and that mandatory testing should be done for C. difficile infection at the onset of the diarrheal syndrome.